An essential role for platelet-activating factor in activating mast cell migration following ultraviolet irradiation. Issue 1 (5th September 2013) - Chacón-Salinas, Rommel; Chen, Limo; Chávez-Blanco, Alma D; Limón-Flores, Alberto Y; Ma, Ying; Ullrich, Stephen E
Abstract : PAF binds to its receptor on mast cells inducing them to migrate from the skin to the lymph nodes, where they mediate immune suppression. ABSTRACT: The UVB (290–320 nm) radiation in sunlight is responsible for inducing skin cancer. Exposure to UV radiation is also immunosuppressive, and the systemic immune suppression induced by UV is a well-recognized risk factor for cancer induction. As UVB radiation is absorbed within the upper layers of the skin, indirect mechanisms must play a role in activating systemic immune suppression. One prominent example is mast cell migration, which from the skin to the draining LN is an essential step in the cascade of events leading to immune suppression. What triggers mast cell migration is not entirely clear. Here, we tested the hypothesis that PAF, a lipid mediator of inflammation produced by the skin in response to UV exposure, is involved. Mast cell-deficient mice (Kit W-sh/W-sh ) are resistant to the suppressive effect of UV radiation, and reconstituting mast cell-deficient mice with normal bone marrow-derived mast cells restores susceptibility to immunosuppression. However, when mast cells from PAFR −/− mice were used, the reconstituted mice were not susceptible to the suppressive effects of UV. Furthermore, PAFR −/− mice showed impaired UV-induced mast cell migration when compared with WT mice. Finally, injecting PAF into WT mice mimicked the effect of UV irradiation and induced mast cell migration but not in PAFR −/− mice. Our findings indicate that PAFR binding induces mast cells to migrate from the skin to the LNs, where they mediate immune suppression.